PHENOTYPIC DETECTION OF EXTENDED SPECTRUM BETA LACTAMASES IN ESCHERICHIA COLI AND KLEBSIELLA PNEUMONIAE ISOLATED FROM PATIENTS AT THE FEDERAL TEACHING HOSPITAL GOMBE, GOMBE STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Klebsiella pneumoniae and Escherichia coli are the major bacterial pathogens being isolated and reported from urine samples worldwide as Extended Spectrum Beta Lactamases (ESBLs) producers. This study was conducted to determine the prevalence of ESBLs producing K. pneumoniae and E. coli from urinary clinical isolates in Federal Teaching Hospital Gombe. A total of two hundred and nine (209) bacterial isolates comprising 100 E. coli and 109 K. pneumonia were collected and recovered on MacConkey agar at 35oC. The isolates were further identified as members of Enterobacteriaceae family using conventional biochemical test. Preliminary screening for ESBL production was carried out using antibiotics disk of ceftadizime (30µg), ceftriazone (30µg) and cefpodozime (10µg) placed on to a surface of Muller-Hinton agar plates, separated from each other by a distance not less than 20mm apart, zones of growth inhibition were measured to the nearest mm. The screened isolates were further confirmed as ESBL producers using Double Disks Synergy Test (DDST). The percentage distribution of ESBL production was 54.13%, 40% and Non ESBL was 45.87% and 60% for K. pneumoniae and E. coli respectively. Majority of ESBL-producing isolates were from young patients, particularly women below 30 years of age. In conclusion, the findings of this study showed an alarming ESBL production in E. coli and K. pneumoniae was observed and recorded among patients receiving health care in FTH Gombe
Keywords: Extended Spectrum Beta Lactamase, E. coli, K. pneumoniae, Urinary clinical isolates